Embracing open science: Understanding data sharing practices, benefits, and challenges at the Malaysian National Institutes of Health - Ahmed, Mahfooz; Roslina Othman; Muhd Zulfadli Hafiz Ismail; Adamu Abubakar Ibrahim; Ali Haji (Malaysian Journal of Library and Information Science, 2025)
This study examines research data sharing practices as a core element of open science at the Malaysian National Institutes of Health (NIH). Using a qualitative research design, semi-structured interviews were conducted with seven heads of departments and units across various NIH institutes and divisions. The study aimed to explore the extent of engagement in data sharing, the perceived benefits of open science, and the challenges faced in implementing such practices within the institutional context. The findings reveal that, while there is general awareness of open science principles, actual data sharing remains limited, with most researchers restricting dissemination to open-access publications. Key benefits cited include enhanced research collaboration, increased visibility and citations, improved transparency and accountability, and greater resource optimisation through reduced duplication. However, significant barriers persist, including inconsistent data management practices, lack of clear ownership guidelines, limited awareness and training, stakeholder sensitivities, and a performance evaluation system that does not reward data sharing. Participants proposed several strategies to address these gaps, including targeted capacity-building initiatives, clearer data-sharing policies, performance-based incentives, upgrades to technical infrastructure, and stronger leadership support from top management. This study provides valuable insights into the organisational and cultural conditions that shape the adoption of open science in Malaysia’s health research sector. The findings have practical implications for policymakers, institutional leaders, and researchers seeking to foster a more transparent, collaborative, and impactful research environment through open science.